Application Of Point of Sales (POS) Application as A Web-Based Clothing Sales Information Media on PT Vearst Cahaya Sejahtera - Putra, Irsan Herlandi (Journal of Current Research In Multidisciplinary, 2024)
The purpose of this study is to determine the benefits of implementing point of sales (POS) applications at PT Vearst Cahaya Sejahtera. The method used in this study is a quantitative method that describes phenomena to answer problem formulations. The formulation of the problem in this study includes (i). How the impact of the application of point of sales (POS) application on sales turnover (ii). How the impact of the application of point of sales (POS) application on company profits. Furthermore, the results of the study (i). The application of point of sales (POS) applications can increase sales turnover (ii). The application of point of sales (POS) applications can increase company profits. The benefit of research is to provide references and information to stakeholders at PT Vearst Cahaya Sejahtera. The development of technology in the retail business is increasingly rapid, companies must be able to adapt quickly and effectively to changes. This technological transformation is a process to respond to changes that occur. Individuals and companies are required to carry out digital transformation. Many companies have carried out digital transformation by implementing the use of point of sales (POS) applications to be able to adapt to these changes. Digital transformation cannot be done casually, it requires a mature understanding and how to manage digital transformation effectively. The method used by the author is to collect journals through the internet and interviews to reach conclusions.